2014
DOI: 10.1093/gbe/evu058
|View full text |Cite
|
Sign up to set email alerts
|

The Peculiar Landscape of Repetitive Sequences in the Olive (Olea europaea L.) Genome

Abstract: Analyzing genome structure in different species allows to gain an insight into the evolution of plant genome size. Olive (Olea europaea L.) has a medium-sized haploid genome of 1.4 Gb, whose structure is largely uncharacterized, despite the growing importance of this tree as oil crop. Next-generation sequencing technologies and different computational procedures have been used to study the composition of the olive genome and its repetitive fraction. A total of 2.03 and 2.3 genome equivalents of Illumina and 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 78 publications
(100 reference statements)
1
51
1
Order By: Relevance
“…The insertion date profiles indicate that Copia and Gypsy REs have experienced similar time courses, with Gypsy REs having replicated more than Copia ones, except during the past million years. Copia and Gypsy amplification histories during the evolution of the host have been described in other species, such as, for example, wheat, in which Copia and Gypsy superfamilies are differently represented in the A and B genomes (Charles et al 2008); rice ); grapevine (Moisy et al 2008); maize (Brunner et al 2005;Wang and Dooner 2006); olive (Barghini et al 2014); sunflower (Ungerer et al 2009;Vukich et al 2009;Cavallini et al 2010;Buti et al 2011;Natali et al 2013); and Norway spruce (Nystedt et al 2013). In general, analysis of plant genomes in a phylogenetic context reveals scarce congruence in RE content and highlights differences in the success of different RE types (Vitte et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The insertion date profiles indicate that Copia and Gypsy REs have experienced similar time courses, with Gypsy REs having replicated more than Copia ones, except during the past million years. Copia and Gypsy amplification histories during the evolution of the host have been described in other species, such as, for example, wheat, in which Copia and Gypsy superfamilies are differently represented in the A and B genomes (Charles et al 2008); rice ); grapevine (Moisy et al 2008); maize (Brunner et al 2005;Wang and Dooner 2006); olive (Barghini et al 2014); sunflower (Ungerer et al 2009;Vukich et al 2009;Cavallini et al 2010;Buti et al 2011;Natali et al 2013); and Norway spruce (Nystedt et al 2013). In general, analysis of plant genomes in a phylogenetic context reveals scarce congruence in RE content and highlights differences in the success of different RE types (Vitte et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The Olea project aims to sequence the olive genome using a strategy of shot-gun sequencing and assembly of short-read sequence data from the Illumina and 454 sequencing platforms (http://genomes.cribi.unipd.it/olive/ wordpress/project/). Recently, Barghini et al (2014) reported that ~31% of the olive genome is composed of tandemrepeats from six main families, two of which were not previously characterized, and it has been estimated that in excess of 70% of the olive genome is composed of repetitive DNA sequence (Barghini et al, 2015). Thus the central challenge of whole-genome shotgun sequence assembly using short-read technologies is resolving repetitive sequences (Schatz et al, 2010), since often these sequences are longer than the read length of the technologies used for sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have used short read sequencing platforms to characterize the olive genome including the sequencing of the olive transcriptome (Alagna et al, 2009, Munõz-Mérida et al, 2013, Kaya et al, 2013, which led to the identification of abundant SNP markers that were successfully used to discriminate Turkish olive cultivars (Kaya et al, 2013). Additionally, Barghini et al (2014), in the context of a project to develop a whole genome sequence for olive, studied the repetitive portion of the olive genome and determined that ~31% of the olive genome is composed of tandem-repeats. Despite an on-going project to sequence the olive genome (Olea project;http://genomes.cribi.unipd.it/olive/wordpress/project/) , there remains a need for a saturated, sequence characterized linkage map for the species, and the SNP data that exists in public databases for olive have so far not been exploited for linkage map development.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted number of protein gene-coding sequences, supported also by RNA sequencing from the different plant tissues, was estimated to be higher than 56,000. Recently, Barghini et al (2014Barghini et al ( , 2015 carried out an analysis of the repeated fraction of the olive genome and reported a peculiar structure of this genome, as compared to that of other plants, with a large percentage of satellite DNA related to a few satellite tandem repeat families Oe80, Oe86, Oe178, Oe179 and Oe218, representing approximately 97% of this class of repeated elements. Among the repeated sequences, retrotransposons represent 40.265%; DNA transposons 5.514% tandem repeats 31.161% of the olive genome.…”
Section: Genomics Studies Genome Sequencingmentioning
confidence: 99%
“…Among the repeated sequences, retrotransposons represent 40.265%; DNA transposons 5.514% tandem repeats 31.161% of the olive genome. In terms of the two-main superfamilies of LTR-retrotransposons, Gypsy and Copia-like LTR are present in a ratio of 1.17:1, indicating that the first ones are more abundant, even if the number of Gypsy families is smaller than the number of Copia, and that the Gypsy retro-transcription event started earlier in the genetic flow of the olive tree genome development (Barghini et al 2014). The characterisation of olive short interspersed nuclear elements (SINEs) nonautonomous retrotransposons was recently carried by Barghini et al (2016) providing one of the first sets of these elements in dicotyledonous species and adding new information on olive genome evolution.…”
Section: Genomics Studies Genome Sequencingmentioning
confidence: 99%